Room with a boo - Myers, Bill; Wimbish, David (Minneapolis, Minn. : Bethany House Publishers, 2002)
With the help of a new invention from Doc, Sean and Melissa win an all-expenses-paid trip to Washington, D.C., where they hope to solve the mystery of a missing helicopter--and of a haunted hotel.
Keywords: Spies; Brothers and sisters; Christian life; Mystery and detective stories